P218 Do specific radiology reporting suggestions influence referral times in active pulmonary tuberculosis?. (December 2018) - Morrison, H; Burn, L; Jones, R; Loughborough, W; Mungall, S
Abstract : Introduction and objectives: Early diagnosis of pulmonary TB (pTB) is essential to prevent transmission and to optimise individual patient outcomes. NICE guidance recommends patients with diagnostic radiology highly suggestive of active pTB should trigger a rapid referral to a multidisciplinary TB team. 1 We looked at cases of pTB diagnosed within our hospitals and whether the suggestions within the radiology report influenced referral time. Methods: We retrospectively identified all patients diagnosed with active pTB at University Hospitals Bristol (UHB) in 2016/2017 from the Enhanced Tuberculosis Surveillance (ETS) register. The radiology of each patient was independently reviewed by a radiologist and a respiratory physician. All patients with pre-diagnosis imaging highly suggestive of active pTB were included in the study. Initial reporting radiologist comments were analysed and time to review by TB team was calculated. Results: 54 cases of active pTB were diagnosed within UHB in 2016/2017. 29 of these had pre-diagnosis imaging that was highly suggestive of active pTB. Requests came from a range of in and out-patient sources. 26/29 radiology reports mentioned TB in the differential diagnosis and of these, 15 made suggestions for referral. Suggestions varied widely and included copying reports to a variety of different clinicians and referral to a range of respiratory clinics. 8 reports suggested referral specifically to the TB team. For out-patients, the average length of time between suggestive radiology and seeing the TB team was 10 days (range 1–28). For those with a report specifically recommending referral to TB services, the average was 5.4 days verses 12.5 days for those without. Conclusion: Radiology remains a key component of TB diagnosis. In our hospitals, we have seen that even if TB is mentioned in the report differential, referral can be delayed without the correct referral pathway being recommended. In pTB, this can result in inferior treatment outcomes and a longer period of potential infectivity. We plan to introduce a specific radiology code with clear referral instructions to our multidisciplinary TB team for all patients with radiology highly suspicious of active pTB. Reference: National Institute for Health and Care Excellence (2016) Tuberculosis(NICE Guideline 33).